Cloning, Expression and Characterization of a Novel Thermophilic Polygalacturonase from Caldicellulosiruptor bescii DSM 6725 - Chen, Yanyan (Molecular Diversity Preservation International (MDPI), 2014)
We cloned the gene ACM61449 from anaerobic, thermophilic Caldicellulosiruptor bescii, and expressed it in Escherichia coli origami (DE3). After purification through thermal treatment and Ni-NTA agarose column extraction, we characterized the properties of the recombinant protein (CbPelA). The optimal temperature and pH of the protein were 72 °C and 5.2, respectively. CbPelA demonstrated high thermal-stability, with a half-life of 14 h at 70 °C. CbPelA also showed very high activity for polygalacturonic acid (PGA), and released monogalacturonic acid as its sole product. The V(max) and K(m) of CbPelA were 384.6 U·mg(−1) and 0.31 mg·mL(−1), respectively. CbPelA was also able to hydrolyze methylated pectin (48% and 10% relative activity on 20%–34% and 85% methylated pectin, respectively). The high thermo-activity and methylated pectin hydrolization activity of CbPelA suggest that it has potential applications in the food and textile industry.